Calcium hypochlorite cytotoxicity mechanism in fibroblasts and effect on osteoblast mineralization - Coaguila-Llerena, Hernán [UNESP]; Ochoa-Rodríguez, Victor Manuel [UNESP]; Passos Barbieri, Isadora [UNESP]; Ramos, Simone Gusmão; Faria, Gisele [UNESP] (Wiley, 2024)
Aim: To determine the cytotoxicity mechanism of 2.5% calcium hypochlorite [Ca(OCl)2] in L929 fibroblasts and the effect of this solution on human osteoblast-like cells (Saos-2) mineralization, compared to that of 2.5% sodium hypochlorite (NaOCl). Methodology: L929 fibroblasts were exposed to Ca(OCl)2 and NaOCl at different dilutions for 10 min. Cell metabolism was assessed by methyl-thiazole-tetrazolium (MTT); lysosome integrity, by neutral red (NR) assay; type of cell death, by flow cytometry (apoptosis/necrosis); cytoskeleton, by actin and α-tubulin fluorescence and cell ultrastructure, by transmission electron microscopy (TEM). The alkaline phosphatase (ALP) activity and mineralized nodule formation were determined in Saos-2 by thymolphthalein release and alizarin red staining (ARS), respectively. The data were analysed by two-way anova and Bonferroni's post-test (α =.05). Results: Ca(OCl)2 promoted higher cell viability and a lower percentage of apoptosis and necrosis than NaOCl (p <.05). Ca(OCl)2 and NaOCl decreased cell metabolism and lysosome integrity, induced the breakdown of microtubules and actin filaments, promoted alterations of rough endoplasmic reticulum and disruption of mitochondrial cristae. Additionally, Ca(OCl)2 did not induce ALP activity and had no effect on mineralized nodules formation. Conclusions: Although Ca(OCl)2 and NaOCl promoted the same cytotoxicity mechanism, Ca(OCl)2 was less cytotoxic than NaOCl. As for ALP activity, no differences were observed between NaOCl and Ca(OCl)2. The production of mineralized nodules induced by Ca(OCl)2 was lower than those induced by NaOCl, but was not different from those induced by the control group.
Keywords: calcium hypochlorite; cell culture techniques; materials testing; root canal treatment; sodium hypochlorite